Development and Mechanical Characterization of Needle-punched Kapok-Flax Nonwovens for Technical Uses - P Pividal; A.M Rocha (Journal of Natural Fibers, 2021)
In this study, sandwich nonwoven fabrics containing raw kapok and flax fibers were developed and produced on a needle-punching processing line for agrotextile/geotextile applications. A two-step approach has been devised to produce nonwovens with compatible mechanical performance. Different structural arrangements were tried, and the mechanical properties of the resulting sandwich fabrics characterized. The nonwoven structures integrating 100% raw kapok fiber layers showed superior mechanical performance, compatible with class III geotextiles.